Suppression of hapten-specific delayed-type hypersensitivity responses in mice by idiotype-specific suppressor T cells after administration of anti-idiotypic antibodies (The Rockefeller University Press, 1979)
Delayed-type hypersensitivity (DTH) responses specific for the phosphorylcholine (PC) hapten were induced in BALB/c mice by immunization with syngeneic peritoneal exudate cells (PEC) coupled with diazotized phenyl-phosphoryl-choline. PC-specific DTH responses were elicited in such immunized mice after footpad challenge with PC- derivatized syngeneic spleen cells. Moreover, PC-immune lymph node cells could passively transfer PC-specific DTH responses to naive BALB/c mice and it was possible to demonstrate that the cells responsible for such passively transferred responses were T lymphocytes. Because the T-15 idiotypic determinant displayed on the TEPC-15 PC-binding myeloma protein is known to be a dominant idiotype associated with anti-PC antibody responses in BALB/c mice, an analysis was made of the effects of anti-T-15 idiotypic antibodies on the induction and expression of murine PC-specific DTH responses. Repeated injections of anti-T-15 idiotypic antiserum, raised in A/J mice by immunization with TEPC-15 myeloma protein, into recipient BALB/c mice both immediately before and after sensitization with PC-PEC virtually abolished the development of PC-specific DTH responses. Although administration of anti-T-15 antiserum effectively inhibited the induction phase of PC-specific DTH responses, these anti-idiotypic antibodies had no suppressive activity at the effector phase of these responses. The inhibition observed with anti-T-15 antibodies was highly specific for the PC hapten, and for PC-specific DTH responses of BALB/c but not A/J mice. Studies were conducted to address the possibility that anti-Id treatment induced suppressor T lymphocytes capable of specifically inhibiting the activity of PC-specific T cells participating in DTH responses. The results demonstrate that idiotype- specific suppressor T cells are, indeed, induced by treatment with anti- Id; moreover, such suppressor T cells, once induced, are highly effective in abrogating both the induction and the effector phases of PC-specific T cell-mediated DTH responses in BALB/c mice.